2015
DOI: 10.1371/journal.pone.0116745
|View full text |Cite
|
Sign up to set email alerts
|

High Density of Tree-Cavities and Snags in Tropical Dry Forest of Western Mexico Raises Questions for a Latitudinal Gradient

Abstract: It has been suggested that a latitudinal gradient exists of a low density of snags and high density of naturally-formed tree-cavities in tropical vs. temperate forests, though few cavities may have characteristics suitable for nesting by birds. We determined snag and cavity density, characteristics, and suitability for birds in a tropical dry forest biome of western Mexico, and evaluated whether our data fits the trend of snag and cavity density typically found in tropical moist and wet forests. We established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
2
8
0
1
Order By: Relevance
“…This may have been influenced by the prevailing south-westerly winds in our study area. The majority of cavities in the study area were rot holes rather than woodpecker breeding cavities, which is similar to that found in other tropical forests (Boyle et al 2008;Cockle et al 2011b;Vázquez and Renton 2015). Therefore, it appears as if the mean orientation of cavities was mainly influenced by wind direction and may be an indirect consequence of the angle of the limbs or branches exposed to wind.…”
Section: Characteristics Of Cavitiessupporting
confidence: 81%
See 1 more Smart Citation
“…This may have been influenced by the prevailing south-westerly winds in our study area. The majority of cavities in the study area were rot holes rather than woodpecker breeding cavities, which is similar to that found in other tropical forests (Boyle et al 2008;Cockle et al 2011b;Vázquez and Renton 2015). Therefore, it appears as if the mean orientation of cavities was mainly influenced by wind direction and may be an indirect consequence of the angle of the limbs or branches exposed to wind.…”
Section: Characteristics Of Cavitiessupporting
confidence: 81%
“…However, the variations in cavity density and characteristics across habitat types have not been well studied in tropical areas. To our knowledge, the only study on cavity characteristics in the tropics is by Vázquez and Renton (2015), who found that compared with semi-deciduous and Piranhea forests, cavities in deciduous forests were fewer and had lower heights and smaller entrance widths, i.e. cavity density and characteristics varied significantly among vegetation types.…”
Section: Introductionmentioning
confidence: 99%
“…However, C. campanisona birds may not always be able to choose their cavities due to limited availability (Vazquez and Renton 2015). As tree cavities are rare in forests, they become a limiting factor for cavity-nesting birds and couples may try to breed in cavities that are unsuited for the purpose (Martin andLi 1992, Martin 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in contrast with temperate forests where avian primary excavators create 77 % of cavities used by secondary-cavity nesters (Martin and Eadie 1999;Martin et al 2004;Aitken and Martin 2007), the majority of cavities in tropical forests are formed naturally through decay processes (Boyle et al 2008;Cockle et al 2011a). Hence, there would appear to be a high density of naturally formed cavities in the tropical and subtropical forests inhabited by many parrot populations Snyder et al 1987;Cockle et al 2008Cockle et al , 2010Váz-quez and Renton 2015), although only a low proportion of these cavities have characteristics that make them suitable for use by secondary cavity-nesting birds (Cockle et al 2010(Cockle et al , 2011bStojanovic et al 2012;Vázquez and Renton 2015).…”
Section: Process Of Nest Cavity Selectionmentioning
confidence: 99%